Wildlife laws monitoring as an adaptive management tool in protected a rea management in Ghana: a case of Kakum Conservation Area - Wiafe, Edward Debrah (SpringerPlus, 2016)
INTRODUCTION: The wildlife laws of Ghana alienated the rural communiti es from forests and material well-being depended upon for their liveli hood and this manifests itself in the progressive conflict between the park patrol staff and poachers from the fringes of the protected area s. CASE DESCRIPTION: The main aim of this study was to determine the i mpact of quantification of patrol efforts on indicators of illegal hun ting activities that occur in rainforest protected areas, as a result of monitoring patrol operations and modifying the original plan. The s pecific objectives were to determine the optimal patrol efforts necess ary to reduce illegal wildlife use to minimal; and the influence of th e rainfall and seasonal activities on illegal wildlife use. DISCUSSION AND EVALUATION: The results indicated that as the patrol efforts incr eased the encounter with illegal wildlife use also increased until a c ertain point that the encounter rates started decreasing. Neither rain fall nor seasonal activities influenced the illegal activities and the patrol efforts. The protection staff of rainforest protected areas wo uld work effectively to bring down illegal wildlife off-take to the ba rest minimum if monitored, quantified and provide feed-back. CONCLUSIO NS: Illegal wildlife off-take can also be reduced by the protection st aff if the original plans are made flexible to be adjusted. Recommenda tions for further studies have been made.